Examining Online Buying and Selling Contracts: A Qualitative Analysis of Marketplace Transactions and Contractual Practices - Sarmadi, Akhmad Sukris; Indrazati, Vina Radhita Putri Margaretha (Interdisciplinary Explorations in Research Journal, 2023)
Abstract This research will discuss how the contract is carried out by sellers and buyers in online buying and selling activities in a marketplace. Nowadays, there are many marketplaces that serve as a place for sellers to sell their goods which are also equipped with various features in it. Considering that the contract is one of the pillars of buying and selling and is a condition for the validity of buying and selling, it is necessary to conduct this research to find out how the contract used in buying and selling carried out in a marketplace. The method used in this research is a qualitative method, with interviews with informants to find out how the practice is and their opinions related to this matter. From the results of this study, it was found that if the goods and prices are clearly known, and there is willingness between the seller and the buyer, then it can be said that the contract and sale are valid because the terms and conditions have been fulfilled and the contract process is complete when the buyer clicks on the order completed/order received. Keywords: Akad, online buying and selling, marketplace. Abstrak Penelitian ini mengulas bagaimana kontrak dilaksanakan oleh penjual dan pembeli dalam kegiatan jual beli online di sebuah marketplace. Saat ini, terdapat banyak marketplace yang berfungsi sebagai tempat bagi penjual untuk menjual barang dagangannya, dilengkapi dengan berbagai fitur di dalamnya. Mengingat bahwa kontrak merupakan salah satu pilar dalam jual beli dan merupakan syarat keabsahan transaksi jual beli, penelitian ini diperlukan untuk mengetahui bagaimana kontrak digunakan dalam kegiatan jual beli di marketplace. Metode yang digunakan dalam penelitian ini adalah metode kualitatif, dengan wawancara bersama informan untuk mengetahui praktik yang dilakukan serta pendapat mereka terkait masalah ini. Dari hasil penelitian ini, ditemukan bahwa apabila barang dan harga jelas diketahui, serta terdapat kesepakatan antara penjual dan pembeli, maka dapat dikatakan bahwa kontrak dan transaksi penjualan tersebut sah karena syarat dan ketentuan telah terpenuhi, dan proses kontrak dianggap selesai ketika pembeli melakukan klik pada "order completed/order received". Kata Kunci: Akad, jual beli online, marketplace.